Land use change in ThapLan National Park, the part of Dong Phra Yayen - Khao Yai Forest Complex World Heritage, Thailand - Pongthep Suwanwaree, Wassana Phanurak and (Naresuan University Journal: Science and Technology (NUJST); Vol 21 No 3 (2013): September-December 2013, 2014)
Land Use and Land Cover Change (LUCC) is a well-recognized agent of ecological change and a prominent interface between human activities and global environmental change. To assess land use classification in ThapLan National Park and the 5 km buffer zone from 1987 to 2006, remote sensing technique was selected. The land use classification in ThapLan National Park and 5 km buffer zone was performed by using 1987, 1997, 2003, and 2006 Landsat-TM data. In this study, ten land use types were 10 land-used types, including Dry Evergreen Forest (DEF), Mixed Deciduous Forest (MDF), Dry Dipterocarp Forest (DDF), paddy field, field crop, perennial and orchard, grassland, water body, urban and built-up area, and other lands (old clearing, uncultivated land, barren land/bare land) based on the classification of Land Development Department (LDD) and the Royal Forest Department (RFD). The maps of land use of ThapLan National Park showed that between 1987 and 2006 the amount of forestland dominantly decreased from 1,948.73 km 2 to 1,890.20 km 2 , while those of the 5 km buffer zone decreased from 1,041.35 km 2 to 973.28 km 2 . The results quantify the land cover change patterns in the tropical forest area and demonstrate the potential of Landsat data to provide an accurate, economical means to map and analyze changes in land cover over time that can be used as inputs to land management and policy decisions. Keywords: Land use classification, ThapLan National Park, Remote sensing technique, Landsat-TM data, Buffer zone
Keywords: Land use classification, ThapLan National Park, Remote sensing technique, Landsat-TM data, Buffer zone